HB-EGF embedded in PGA/PLLA scaffolds via subcritical CO2 augments the production of tissue engineered intestine. (October 2016) - Liu, Yanchun; Nelson, Tyler; Cromeens, Barrett; Rager, Terrence; Lannutti, John; Johnson, Jed; Besner, Gail E.
Abstract: The ability to deliver sustained-release, biologically active growth factors through custom designed tissue engineering scaffolds at sites of tissue regeneration offers great therapeutic opportunity. Due to the short in vivo half-lives of most growth factors, it is challenging to deliver these proteins to sites of interest where they may be used before being degraded. The application of subcritical CO2 uses gas-phase CO2 at subcritical pressures ranging from 41 to 62 bar (595–913 PSI) which avoids foaming by reducing the amount of CO2 dissolved in the polymer and maintains completely reversible plasticization. In the current study, heparin-binding EGF-like growth factor (HB-EGF) was embedded into polyglycolic acid (PGA)/Poly-l -latic acid (PLLA) scaffolds via subcritical CO2 exposure for the production of tissue engineered intestine (TEI). PGA fiber morphology after subcritical CO2 exposure was examined by scanning electron microscopy (SEM) and the distribution of HB-EGF embedded in the scaffold fibers was detected by HB-EGF immunofluorescent staining. In vivo implantation of HB-EGF-embedded scaffolds confirmed significantly improved TEI structure as a result of local delivery of the trophic growth factor. These findings may be critical for the production of TEI in the treatment of patients with short bowel syndrome in the future.